66‐4: High Brightness Active Matrix Micro‐LEDs with LTPS TFT Backplane. Issue 1 (30th May 2018) - Kim, Hyo-Min; Um, Jae Gwang; Lee, Suhui; Jeong, Duk Young; Jung, Younghun; Lee, Sang Hern; Jeong, Tak; Joo, Jaeyoung; Hur, Jeongwook; Choi, Jong Hwa; Kwak, Joon Seop; Jang, Jin
Abstract : We report the active matrix micro‐LEDs (AMLEDs) with high brightness over 40, 000 cd/m 2 . Active‐matrix low temperature poly‐Si TFT with mobility over 150 cm 2 /Vs by using blue laser annealing is used for AMLEDs. A 256 pixels micro‐LED with ~ 40, 000 cd/m 2 at the driving current of 10 mA is fabricated and then 1, 024 pixels micro‐LED is demonstrated using Au bonding on the LTPS TFT backplane.